Automatic defect detection in wind turbine blades: A Deep Learning Model Pipeline for Detection and Classification of Defects in Drone Images - Neves, Lara Souto das (2022)
Project Work presented as the partial requirement for obtaining a Master's degree in Data Science and Advanced Analytics, specialization in Data Science